Performance analysis of full-duplex relay-aided NOMA systems using partial relay selection - Tregancini, Anderson [UNESP]; Olivo, Edgar Eduardo Benitez [UNESP]; Osorio, Diana Pamela Moya; De Lima, Carlos H. M.; Alves, Hirley (Institute of Electrical and Electronics Engineers (IEEE), 2020)
Capitalizing on the benefits of non-orthogonal multiple access (NOMA) and full-duplex relaying as key technologies to boost spectral efficiency in the next generation of wireless communications, herein we investigate the performance of a cooperative network in which a source communicates with two destinations via one node selected from a set of full-duplex amplify-and-forward relays. For this purpose, a power-domain NOMA scheme is used to transmit information from the source to the destinations, and partial relay selection is performed to choose the relay based on the channel state information of the first hops. The system performance is characterized in terms of both the outage probability and the ergodic capacity, for which, exact analytical expressions are derived in integral form. In addition, to reduce the computational complexity of the obtained analytical results, closed-form expressions are derived from lower-bound, approximate, and asymptotic analyses. From these analytical expressions, the impact on the system performance of the number of relays, the power allocation factor between the NOMA destinations, and the residual self-interference at full-duplex relays is assessed. The correctness of our analyses is validated by Monte Carlo simulations, and a comparison with the half-duplex relay-aided NOMA system counterpart is also provided.
Keywords: Amplify-and-forward; ergodic capacity; full-duplex relaying; NOMA; outage probability; partial relay selection